Bonding characteristics of aerogel to composite - Lim, Yau Hui. (2010)
Aerogels are the lightest solid that exists. Despite being light, aerogel has high strength to weight ratio but it is rarely used by industries. The aviation industry today is looking towards creating a lighter and stronger composite. Aerogel is the material that is being looked at as it has the desired properties.